An investigation on pattern of unstable "Beta-Gamma (βγ)" magnetic classification of sunspot in type II burst, type III burst and type IV burst on active region / Siti Nur Umairah Sabri - Sabri, Siti Nur Umairah (2019)
The pattern of unstable "Beta-Gamma (βγ)" magnetic classification of sunspot has been investigated. From previous study, it has reported Delta (5) sunspot correlates well with flares productivity thus lead to major flares. However, based on data collected, it shows that βγ sunspot has tendency to produce major flares as it seen to be the highest formation compared to the other types of magnetic classification of sunspot included Delta(5) sunspot. In this study, the pattern of the unstable βγ sunspot occurred within 5 years, from 2012 till 2016 shows different pattern for each type of magnetic classification. βγ sunspot followed 11-year solar cycle and moved faster at equator compared at the edge of solar disk of the Sun.